A review of rotavirus vaccine use in Asia and the Pacific regions: challenges and future prospects. (2nd December 2021) - Buchy, Philippe; Chen, Jing; Zhang, Xu-Hao; Benninghoff, Bernd; Lee, Christa; Bibera, Gyneth Lourdes
ABSTRACT: Introduction: Rotavirus infection causes a significant proportion of diarrhea disease burden in children <5 years of age in Asia and the Pacific regions. The World Health Organization recommends that rotavirus vaccination should be included in national immunization programs to prevent rotavirus gastroenteritis (RVGE). Areas covered: A literature review was performed to identify and summarize published evidence on RVGE epidemiology and status of rotavirus vaccine use, including the impact and cost-effectiveness of rotavirus vaccination programs in Asia and the Pacific regions (49 countries) during the period 2000–2018. Expert opinion: Rotavirus vaccination programs have successfully reduced the burden of RVGE in many countries. However, such programs still do not exist in most Asia-Pacific countries, and therefore the burden of RVGE remains high in children <5 years of age. Challenges to vaccine implementation include a lack of surveillance data; safety concerns around intussusception; a general lack of awareness about RVGE disease epidemiology and vaccines among physicians, policy-makers, and parents; insufficient cost-effectiveness analyses; and potential issues with vaccine affordability including vaccination costs and lack of political will. Recommendations to overcome these challenges include developing cost-effectiveness analyses for more diverse national and regional settings, providing non-governmental support for low-income countries, and improving advocacy efforts. PLAIN LANGUAGE SUMMARY: What is the context? Rotavirus (RV) infection causes acute gastroenteritis (GE) in children under 5 years of age. Rotavirus vaccination (RVV) implementation has been slow in Asia and the Pacific (AP) regions, which could be responsible for the region falling behind in their fight against RVGE. What is new? RVV via national immunization programs (NIPs) is available in 8/49 countries and through the private market or non-governmental support in other countries. Coverage rates vary between countries, possibly driven by the mechanism through which RVV is available. A substantial positive impact of RVV on RVGE disease burden with a very low risk of intestinal intussusception for up to 7 days after RVV has been documented in the AP regions. Economic evaluation studies, mainly cost-effectiveness analyses, predict a significant reduction in treatment costs related to RVGE and its complications showing that RVV is good value for money. What is the impact? The prospect of continued safe and effective use of RVV in the AP regions is promising. Challenges to RVV implementation include establishing evidence of burden of disease, poor awareness of rotavirus vaccines, limited evidence from cost-effectiveness analyses from several countries, issues of affordability of the vaccine and a lack of political will. Recommendations for RVV implementation into the NIPs include conducting clinical and cost-effectiveness studies in countries where these are not available, establishing reliable surveillance mechanisms, providing non-governmental support for low-income countries and improving advocacy efforts. Maintenance of high vaccination coverage is needed in countries that have implemented national RVV programs. Graphical abstract